Meningkatkan Kemandirian Melalui Discovery Learning Berbantuan LKPD Materi Manusia Makhluk Pribadi Kelas X SMKN1 Putussibau - Faustian Kalis (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The implementation of Catholic Religious Education and Character Education in class X SMKN 1 Putussibau, it was found that, first: students were not actively involved in learning activities, so they faced difficulties in understanding and applying the concepts being taught. Second, the learning model used with the material being taught is not quite right. Third, in the learning process, the teacher has not linked the dimensions of the Pancasila Student Profile significantly. Based on the existing problems, it is necessary to immediately make improvements in the learning process. The improvement in question is integrating the dimensions of the Pancasila student profile. The purpose of this research is to increase independence and increase student learning achievement. This type of research is descriptive qualitative. The subjects were 13 class X students of SMK Negeri 1 Putussibau. The results showed that in the first cycle the percentage of independence was only 69.78%. Then continued in cycle II, the percentage of student independence increased to 92.86%. This shows that the percentage of independence of students has increased and achieved predetermined indicators of success. Learning achievement has also increased. In cycle I, the percentage of learning achievement was 69.2%. The percentage of student learning achievement in cycle II increased to 84.6%. So it can be concluded that the discovery learning model assisted by LKPD can increase the independence and learning achievements of students in class X phase E SMKN 1 Putussibau.